(untitled) (Research, Society and Development, 2020)
The response plan is the result of actions and requires systemic and integrated strategies that support, welcome and guide people, families and society in sharing responsibilities in caring for themselves and the other. The objective is to report the professional experience in the construction of a response plan for a Prevention and Coping Office to COVID-19. It is a report of professional experience on the construction of a response plan for the Office of a municipality in the interior of the State of Rio Grande do Sul. the pandemic of the new coronavirus responsible for COVID 19. These actions, through the use of a predefined coordination system, allowed an adequate articulation and better use of resources and optimization of results. In view of the responses presented, in addition to allowing the community in general to know the step by step of a municipality in the face of a public health emergency, it makes it possible to strengthen actions beyond this pandemic.